Experiential learning: the Kuching project - Wan Mohamad, Wan Srihani; Ismail, Ida Suriana; Mohd Noor, Mohd Zairul; Ismail, Zamri (2012)
This paper discusses on a final project of third year Architecture module. The project selected was the Habitat for Humanity (HFH) regional office in Kuching, Sarawak. The studio tutors has posited the idea of bringing studio outside the classroom and implemented Student-Centred Learning (SCL) towards another milestone. The project has allowed the development of exploration studio outside the classroom approach. The project was divided into two parts; which the first part the students were involved in a design proposal for the needy, brainstorming on the idea of new possible layout, requirements, alternative design with costing awareness and subsequently, the students are exposed to a real hands-on construction of housing for needy in Jalan Matang Kuching, Sarawak. While the primary motivation underlying this project is to promote innovation in studio project, a substantial component of the study involved gaining a broader perspective of humanistic approach in architectural thoughts and awareness among the students outside their comfort studio room. The state of the art of the studio project has been explored by bringing it outside the studio context, working in a group, meeting tight deadlines, exploring contexts and concepts within short amount of time and preparing the students for an industrial environment for their future. This auspicious project specifically focuses on graduating students of final year Bachelor of Design (Architecture) UPM with the noble intention to request of their balance in producing architectural products and to invoke their thinking and maturity in response to real deal. Thus, the outcomes of the project provide i) the insight of the two weeks trip to Kuching, Sarawak, ii) the design proposal of the Habitat House for the needy and iii) the development of the final design of HFH regional office in Sarawak with the final outcomes of the design proposal. In summary, the project will highlight on the issue of architectural for humanity aspects and contributes to the innovations of education and studio projects for architectural education in Malaysia.